IL4I1 Accelerates the Expansion of Effector CD8+ T Cells at the Expense of Memory Precursors by Increasing the Threshold of T-Cell Activation - Puiffe, Marie-Line; Dupont, Aurélie; Sako, Nouhoum; Gatineau, Jérôme; Cohen, José L.; Mestivier, Denis; Lebon, Agnès; Prévost-Blondel, Armelle; Castellano, Flavia; Molinier-Frenkel, Valérie (Frontiers in Immunology, 2020)
IL4I1 is an immunoregulatory enzyme that inhibits CD8 T-cell proliferation in vitro and in the tumoral context. Here, we dissected the effect of IL4I1 on CD8 T-cell priming by studying the differentiation of a transgenic CD8 T-cell clone and the endogenous repertoire in a mouse model of acute lymphochoriomeningitis virus (LCMV) infection. Unexpectedly, we show that IL4I1 accelerates the expansion of functional effector CD8 T cells during the first several days after infection and increases the average affinity of the elicited repertoire, supporting more efficient LCMV clearance in WT mice than IL4I1-deficient mice. Conversely, IL4I1 restrains the differentiation of CD8 T-cells into long-lived memory precursors and favors the memory response to the most immunodominant peptides. IL4I1 expression does not affect the phenotype or antigen-presenting functions of dendritic cells (DCs), but directly reduces the stability of T-DC immune synapses in vitro, thus dampening T-cell activation. Overall, our results support a model in which IL4I1 increases the threshold of T-cell activation, indirectly promoting the priming of high-affinity clones while limiting memory T-cell differentiation.